2018
DOI: 10.3389/fmicb.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical and Biological Fungicides Applied to Grapevine on Grape Biofilm, Must, and Wine Microbial Diversity

Abstract: This study was aimed to measure the impact of the application of a bio-fungicide against Botrytis cinerea on the microbiota involved in the alcoholic fermentation (AF) of Tempranillo Rioja wines. For this purpose, a bio-fungicide composed of the biological control bacterium Bacillus subtilis QST713 was applied to the vineyard. The microbial diversity was analyzed from grape biofilm to wine. Impact on microbial diversity was measured employing indexes assessed with the software PAST 3.10 P.D. Results were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
(56 reference statements)
4
31
0
1
Order By: Relevance
“…On the other hand, the fact that this yeast only appears at the end of the ripening process may be due to the application of antifungal treatments during most parts of the period in which the samples were collected, except in the last week, during which there was no treatment applied. This hypothesis seems to fit with certain studies about antifungal treatments that produced a decrease in the yeast population [20,33,34]. Some of the microorganisms described in this work are not the common type of yeast founded on grape surface.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the fact that this yeast only appears at the end of the ripening process may be due to the application of antifungal treatments during most parts of the period in which the samples were collected, except in the last week, during which there was no treatment applied. This hypothesis seems to fit with certain studies about antifungal treatments that produced a decrease in the yeast population [20,33,34]. Some of the microorganisms described in this work are not the common type of yeast founded on grape surface.…”
Section: Discussionsupporting
confidence: 86%
“…[1,13], and spoilage yeasts (such as Dekkera bruxellensis, Zygosaccharomyces bailii ) responsible for wine alterations [14,15]. Several studies reported that one of the most important factors that influences microbial community composition associated with grape berries are the vineyard agronomic practices [5,16,17,18,19,20,21,22,23]. Indeed, Cordero-Bueso and co-workers [20] showed a greater biodiversity of yeast species when the vineyard was treated with organic practices instead conventional ones.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Comitini and Ciani [5] found a reduction in the yeast diversity when organic fungicides were applied. More recently, Escribano-Viana et al [23] found that the bio-fungicide did not show significant impact on the wine microbiota whereas the chemical fungicide caused a reduction of microbial community richness and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…And soil enzyme activities have been reported to be greatly affected by soil microbial properties because transformations of the important organic elements occur through microorganisms [26]. It is reported that the biofungicide had no significant impact on the wine microbiota, whereas the chemical fungicide caused a reduction of microbial community richness and diversity [27].…”
Section: Introductionmentioning
confidence: 99%